Mesenchymal Stem Cell Therapy in Diabetes Mellitus: Progress and Challenges - El-Badri, Nagwa; Ghoneim, Mohamed A. (Journal of Nucleic Acids, 2013)
Advanced type 2 diabetes mellitus is associated with significant morbidity and mortality due to cardiovascular, nervous, and renal complications. Attempts to cure diabetes mellitus using islet transplantation have been successful in providing a source for insulin secreting cells. However, limited donors, graft rejection, the need for continued immune suppression, and exhaustion of the donor cell pool prompted the search for a more sustained source of insulin secreting cells. Stem cell therapy is a promising alternative for islet transplantation in type 2 diabetic patients who fail to control hyperglycemia even with insulin injection. Autologous stem cell transplantation may provide the best outcome for those patients, since autologous cells are readily available and do not entail prolonged hospital stays or sustained immunotoxic therapy. Among autologous adult stem cells, mesenchymal stem cells (MSCs) therapy has been applied with varying degrees of success in both animal models and in clinical trials. This review will focus on the advantages of MSCs over other types of stem cells and the possible mechanisms by which MSCs transplant restores normoglycemia in type 2 diabetic patients. Sources of MSCs including autologous cells from diabetic patients and the use of various differentiation protocols in relation to best transplant outcome will be discussed.